Aspirin Reduces the Incidence of Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Receiving Oral Nucleos(t)ide Analog - Hui, Vicki Wing-Ki; Yip, Terry Cheuk-Fung; Wong, Vincent Wai-Sun; Tse, Yee-Kit; Chan, Henry Lik-Yuen; Lui, Grace Chung-Yan; Wong, Grace Lai-Hung (Clinical and translational gastroenterology, 2021)
Aspirin may reduce the risk of chronic hepatitis B (CHB)-related hepatocellular carcinoma (HCC) in patients receiving antiviral treatment. We aimed to investigate the impact of aspirin on reducing HCC risk in patients treated with first-line oral nucleos(t)ide analogs (NAs; entecavir and/or tenofovir disoproxil fumarate). We conducted a territorywide, retrospective cohort study in NA-treated CHB patients between 2000 and 2018 from the electronic healthcare data repository in Hong Kong. Subjects were classified into aspirin users for at least 90 days during NA treatment (aspirin group) or no aspirin or any other antiplatelet use during follow-up period (no aspirin group). Incidence rates of HCC and gastrointestinal bleeding (GIB) in 2 groups with propensity score matching with 1:3 ratio. Of 35,111 NA-treated CHB patients of mean age of 53.0 years and 61.6% men, sixty-nine (4.0%) and 1,488 (4.5%) developed HCC at a median (interquartile range) of 2.7 (1.4-4.8) years and 3.2 (1.8-6.0) years in the aspirin group and no aspirin group, respectively. A duration-dependent association between aspirin and the risk of HCC was observed (subhazard ratio [sHR] 3 months-2 years: 0.65; 95% confidence interval [CI] 0.47-0.92; sHR 2-5 years: 0.63; 95% CI 0.43-0.94; sHR from ≥5 years: 0.41; 95% CI 0.18-0.91). Patients who took aspirin for ≤2 years had significantly higher risk of GIB (sHR: 1.73, 95% CI 1.07-2.79) than those not receiving aspirin. The risk of GIB started declining with the longer use of aspirin and becoming insignificant for ≥5 years' use (sHR: 0.79, 95% CI 0.19-3.21). Long-term aspirin use is associated with a lower risk of HCC in a duration-dependent manner in NA-treated CHB patients without a significant increase in the risk of gastrointestinal adverse effects.